2021
DOI: 10.3847/1538-4357/ac1dae
|View full text |Cite
|
Sign up to set email alerts
|

The IGRINS YSO Survey II: Veiling Spectra of Pre-main-sequence Stars in Taurus-Auriga

Abstract: We present measurements of the H- and K-band veiling for 141 young stellar objects (YSOs) in the Taurus-Auriga star-forming region using high-resolution spectra from the Immersion Grating Near-Infrared Spectrometer. In addition to providing measurements of r H and r K , we produce low-resolution spectra of the excess emission across the H and K bands. We fit temperatures to the excess spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The Lyα flux ratios and veiling measurements are statistically significantly positively correlated (Spearman ρ = 0.60, p = 0.006), showing that increased veiling generally corresponds to P Cygni-like Lyα emission lines. We also find a strong negative correlation between the H I velocities and the K-band veiling measurements (Spearman ρ = −0.66, p = 0.0006), consistent with the disappearance of T ∼ 2000 K dust that fills in the intrinsic protostellar spectrum (see, e.g., Kidder et al 2021). This may indicate a depletion of inner disk material as outflowing winds slow by shifting to larger radii and infalling accretion flows become the dominant absorber of Lyα photons, although r K may also be influenced by the inner disk inclination or scale height that we cannot measure from these observations (see, e.g., Johns-Krull & Valenti 2001).…”
Section: Model H I Velocities Probe Kinematics Of Accretion and Outflowssupporting
confidence: 80%
“…The Lyα flux ratios and veiling measurements are statistically significantly positively correlated (Spearman ρ = 0.60, p = 0.006), showing that increased veiling generally corresponds to P Cygni-like Lyα emission lines. We also find a strong negative correlation between the H I velocities and the K-band veiling measurements (Spearman ρ = −0.66, p = 0.0006), consistent with the disappearance of T ∼ 2000 K dust that fills in the intrinsic protostellar spectrum (see, e.g., Kidder et al 2021). This may indicate a depletion of inner disk material as outflowing winds slow by shifting to larger radii and infalling accretion flows become the dominant absorber of Lyα photons, although r K may also be influenced by the inner disk inclination or scale height that we cannot measure from these observations (see, e.g., Johns-Krull & Valenti 2001).…”
Section: Model H I Velocities Probe Kinematics Of Accretion and Outflowssupporting
confidence: 80%
“…However, to draw this conclusion, we assumed that these inner disk indicators, such as the slope of the spectral energy distribution, are suitable inner disk diagnostics. Kidder et al (2021) showed that some of the targets classified as Class III using these disk indicators still show some inner disk emission based on the K band excess. They checked the emission excess of V819 Tau, which we used as a template to compute the veiling, but the H and K excesses found were very small, similar to the systematic veiling we obtained in Sect.…”
Section: Veiling Compared To Inner Disk Diagnosticsmentioning
confidence: 99%
“…The veiling in the optical and in the IR wavelengths has been studied using different approaches in the aim to understand its origins and variability (e.g., Basri & Batalha 1990;Edwards et al 2006;Fischer et al 2011;Antoniucci et al 2017;Gully-Santiago et al 2017;Ingleby et al 2013;McClure et al 2013;Kidder et al 2021). The veiling variability along the stellar spectra depends on wavelength (e.g., Fischer et al 2011;Faesi et al 2012;McClure et al 2013;Rei et al 2018), and optical veiling is often associated with the accretion process, while the accretion shock is thought to be at the origin of an additional continuum emitting source to the stellar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The veiling in the optical and in the IR wavelengths has been studied using different approaches in the aim to understand its origins and variability (e.g., Basri & Batalha 1990;Edwards et al 2006;Fischer et al 2011;Antoniucci et al 2017;Gully-Santiago et al 2017;Ingleby et al 2013;McClure et al 2013;Kidder et al 2021). The veiling variability along the stellar spectra depends on wavelength (e.g., Fischer et al 2011;Faesi et al 2012;McClure et al 2013;Rei et al 2018), and optical veiling is often associated with the accretion process, while the accretion shock is thought to be at the origin of an additional continuum emitting source to the stellar spectrum.…”
Section: Introductionmentioning
confidence: 99%